Shallow submarine mud volcano in the northern Tyrrhenian sea, Italy. (November 2020) - Saroni, Anna; Sciarra, Alessandra; Grassa, Fausto; Eich, Andreas; Weber, Miriam; Lott, Christian; Ferretti, Giacomo; Ivaldi, Roberta; Coltorti, Massimo
Abstract: Submarine methane emissions in the Tuscan Archipelago have been studied since the 1960s, both for economic and research purposes. Offshore gas seepage is mainly concentrated southward and westward of Elba island, along N–S faults related to recent extensional activity in the Tuscan shelf and N–S trending positive magnetic anomalies, which have been interpreted as serpentinites associated with ophiolitic rocks due to their very high magnetic susceptibility. This study focuses on the gas chemistry of a new emission site corresponding to a shallow water mud volcano in the Scoglio d'Affrica area. The Scoglio d'Affrica seep has a gas composition typical of mud volcanoes, with methane as the prevalent component (95 vol%) and minor gases which include carbon dioxide, nitrogen and trace amounts of helium. The combined stable C and H isotope composition of CH4 (δ 13 C and δ 2 H) and the enrichment in heavy carbon isotopes of CO2, highlight a prevalent secondary microbial origin for these fluids (δ 13 C~−35.8‰ vs VPDB; δ 2 H~−166‰ vs VSMOW; δ 13 CCO2 up to + 21.7‰ vs VPDB). Thus, in spite of the occurrence of positive magnetic anomalies, a possible abiotic origin of methane is excluded. Moreover, the gas from the mud volcano is extremely depleted in 3 He and presents typical 3 He/ 4 He ratios of a geological setting in which radiogenic crustal helium is strongly predominant. A photo-mosaic of the mud volcano is also reported. A possible connection with other submarine methane emissions in the Tuscan Archipelago is limited to emissions located few kilometers from the Scoglio d'Affrica area. Recent emissions in the area suggest that gases similar in composition from distinct reservoirs, find their way to the surface from Eocene deposits in different time intervals and through different faults and fractures, placed along the Elba-Pianosa ridge. Highlights: A photo-mosaic of the shallowest mud volcano in the Tyrrheanian Sea is reported. Analysis of isotopic and molecular composition of submarine methane emissions. Carbon dioxide is enriched in heavy carbon isotopes. Radiogenic crustal helium reveals discontinuities in shallow crustal levels. Secondary microbial origin is predominant; abiotic origin is discarded.